Expanding agent for well cementation cementing material and application of expanding agent
The expansion agent that prepares and wraps the expansion components through high-temperature calcination solves the problem of the narrow temperature and mismatch of the expansion effect of the existing expansion agent, and realizes the expansion effect synergistically with the cement hydration process, and improves the cementing quality.
Patent Information
- Application Number
- CN202411983158.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing expansion agent for cementing cementing materials has a narrow temperature range, and the expansion process does not match the cementing cement hydration process, resulting in a decrease in cementing quality.
The expansion agent clinker is prepared by high-temperature calcination, and the expansion components are wrapped with cement mineral materials to achieve the synergistic effect of the expansion agent expansion process and the cement hydration process.
The effect of the expansion agent is improved, the cementing quality is enhanced, and the cementing quality and compressive strength of the cement ring are ensured.
Smart Images

Figure CN119683893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas well cementing materials, and more specifically to an expansion agent for cementing gelling materials and its application. Background Art
[0002] Cementing is an important part of the development of oil and gas resources. The quality of cementing cement ring is crucial to ensure the long-term safe production of oil and gas wells. The bonding quality of the first and second bonding surfaces of cementing cement ring is an important factor affecting the quality of cementing. The better the bonding state between cement and formation and casing, the better the cementing quality. The existing cement slurry system mainly uses silicate cement as a cementing material. During the solidification and hardening process of silicate cement, the specific gravity of the reactant is lower than that of the reaction product, and the volume of cement stone will produce "chemical shrinkage", resulting in a decrease in the bonding quality of the cement ring. In severe cases, it will crack and form micro gaps. Studies have shown that gas channeling can occur when there is a 0.01mm micro gap at the cement ring interface. When the micro gap is 0.05-0.07mm, it will lead to unqualified cementing quality.
[0003] In order to avoid the problem of reduced interface bonding quality caused by volume shrinkage of oil well cement, it is usually necessary to add a certain amount of expansion agent to the cementing slurry, hoping that the volume expansion generated by the expansion agent can offset the volume shrinkage of cement hydration process and achieve the purpose of improving cementing quality. At present, there are two main types of expansion agents used in oil well cement: gas-generating expansion agents (hydrogen, nitrogen, etc.) and lattice expansion agents (expansion agents calcium vanadate, free lime and periclase, etc.). Gas-generating expansion agents mainly use the gas generated by the reaction of alkali-active metal powder with the alkaline solution in the cement slurry as the expansion source. They are suitable for low-pressure environments and shallow wells. The gas generation time is controlled by temperature and has a narrow range of use. Lattice expansion agents mainly compensate for the volume shrinkage that occurs during cement hardening and improve the cement stone structure to a certain extent by generating calcium vanadate, hydrogen free lime, hydrogen periclase, etc.
[0004] CN101481605A discloses a cement expansion agent, which improves the expansion performance of cement paste by adding calcium raw materials, magnesium raw materials, silicon aluminum raw materials and modified materials, and the plastic expansion rate of cement paste can reach 1%-3%. However, referring to the comparative examples and examples, the comparative test found that the effect above 95°C is not ideal, and it can only effectively control the compressive strength of cement paste after 24 hours of curing. CN111454032A discloses a toughening expansion agent for cementing cement paste and a tough micro-expansion cement paste system, which improves the expansion performance and toughness of cement paste by adding magnesium oxide particles, aluminum oxide particles, calcium oxide particles, and calcium carbonate whiskers, but does not significantly improve the compressive strength of cement paste. The above expansion agents all have certain side effects, that is, the expansion agents will cause the strength of cement paste to decline.
[0005] Since the cementing operation environment has the characteristics of a wide temperature range and complex environment, when the cementing formation temperature is high, the expansion agent reacts too quickly. In order to delay the action time of the expansion agent, a treatment process of encapsulating organic polymers is currently used to achieve the effect of delaying the expansion reaction through polymer encapsulation. However, this method is limited by the properties of the polymer, the decomposition temperature of the polymer shell is relatively narrow, and there is also the problem of a narrow applicable temperature range. Summary of the invention
[0006] In order to overcome the defects and deficiencies in the above-mentioned prior art, the present invention provides an expansion agent for cementing cementing materials. The purpose of the present invention is to solve the problem that the applicable temperature range of the existing expansion agent for cementing cementing materials is narrow and the expansion process does not match the cement hydration process of cementing. The present invention prepares the expansion agent clinker by high-temperature calcination, and uses cement mineral materials to wrap the expansion component to achieve the synergistic effect of the expansion process of the expansion agent and the cement hydration process, thereby improving the effect of the expansion agent and achieving the purpose of improving the cementing quality.
[0007] In order to solve the above problems existing in the prior art, the present invention is implemented through the following technical solutions.
[0008] The first aspect of the present invention provides an expansion agent for cementing cementing material, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them; In parts by weight, the expansion agent raw material comprises Calcium materials: 30-70 parts, magnesium materials: 10-30 parts, iron and aluminum materials: 12-35 parts, other materials: 0-10 parts; The mineral composition of the expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are wrapped by tetracalcium aluminoferrate.
[0009] Further preferably, the applicable temperature of the expansion agent is 30°C-90°C.
[0010] Further preferably, the chemical composition of the expander raw material is controlled within the range of SiO2≤3.5%, SO3>2.4%, and Al2O3:Fe2O3>0.64%.
[0011] Further preferably, the particle distribution of the calcareous material is V 45μm-200μm ∈[35%, 60%], particles with a particle size greater than 200 μm <5%; the particle distribution in the magnesium material is V 45μm-200μm ∈[35%,60%], particle size greater than 200μm particles <5%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm ∈[25%,40%], particles with a size greater than 200μm <2%.
[0012] More preferably, the calcareous material is any one or any combination of a mixture of carbide slag and limestone, marble and white mud, wherein the CaO content is ≥52.00% and SiO2 ≤1.5%.
[0013] More preferably, the magnesia material is any one or more combinations of dolomite, magnesite and sepiolite, wherein the MgO content in dolomite is ≥19.00%, the MgO content in magnesite is ≥40.00%, and the MgO content in sepiolite is ≥19.0%.
[0014] Further preferably, the iron material in the iron and aluminum materials is copper slag, magnetite, sulfuric acid slag or steel slag, and the F2O3 content is ≥50.00%; the aluminum material in the iron and aluminum materials is bauxite, aluminum ash slag or high-iron bauxite, wherein the Al2O3 content in bauxite is ≥70.00%, SiO2≤2.0, the aluminum content in aluminum ash slag is ≥65.00%, SiO2≤2.0, the Al2O3 content in high-iron bauxite is ≥29.00%, and the F2O3 content is ≥15.00%.
[0015] More preferably, the other materials are fluorite and dihydrate gypsum, anhydrite, mixed gypsum, desulfurized gypsum, phosphogypsum or fluorite, wherein the F ion content in the fluorite is ≥25.00%, and the SO3 content in the gypsum is ≥30.00%.
[0016] Further preferably, the specific surface area of the expansion agent is controlled within a range of 240-300 m 2 / kg.
[0017] The expansion agent mentioned in the first aspect is used in cementing gelling materials in an amount of 5%-10% by mass of the cementing gelling materials.
[0018] Compared with the prior art, the beneficial technical effects brought by the present invention are as follows: 1. The present invention controls the raw material particle size in a differentiated manner, adopts low-temperature calcination, adopts trace elements to control the liquid phase viscosity, regulates the distribution state of different minerals, realizes the step-by-step expansion of different expansive components in silicate cement, and participates in the hydration reaction of silicate cement, thereby achieving the function of compensating for shrinkage and controlling expansion, and realizing the purpose of synergistic expansion reaction of the expansive agent and cement hydration reaction.
[0019] 2. The advantages of this expansion agent and other expansion agents are that the use of calcium materials, iron materials, aluminum materials and other materials can use waste and make rational use of resources, realizing the greening and resource utilization of waste, which has certain social benefits and provides technical support and guarantee for the early realization of carbon peak and carbon neutrality.
[0020] 3. Control the particle size of raw materials in steps: increase the coarse particle content of the raw materials of the main expansion minerals - free calcium oxide and periclase, and increase the specific surface area of free calcium oxide and periclase particles; greatly increase the iron and aluminum content, and increase the amount of liquid phase; reduce the particle size of aluminum and iron materials, reduce the liquid phase viscosity, increase the liquid phase fluidity and encapsulation; add suitable mineralizers - fluorite and gypsum to adjust the liquid phase viscosity, etc. to adjust the liquid phase to achieve the encapsulation of free calcium oxide and periclase by iron.
[0021] 4. The particle size of the expansive agent is controlled by the specific surface area method. The hydration speed of the three main mineral components in the expansive agent and cement is adjusted by the size, so as to achieve the synergistic reaction of compensating shrinkage and micro-expansion and hydration reaction and achieve a tighter bonding performance between cement stone and casing.
[0022] 5. The calcination and hydration reaction mechanism of the expansion agent of the present invention is: ——During the calcination process, the content of alumina and iron oxide in the raw materials is adjusted to promote the solid phase reaction of active calcium oxide, active iron oxide and active alumina to form dicalcium ferrite and calcium aluminate. As the temperature rises, dicalcium ferrite continuously dissolves calcium aluminate to form a liquid phase with lower viscosity. Compared with silicate cement clinker, the amount of liquid phase also increases. When the remaining calcium oxide cannot react with calcium aluminate, free calcium oxide is formed; magnesium oxide is easily dissolved in the iron phase to form a eutectic solution, and the remaining magnesium oxide cannot be dissolved in the liquid phase, and periclase is formed during the cooling process. The eutectic solution has a lower liquid phase viscosity under high temperature conditions, which can achieve the encapsulation of free lime and active magnesium oxide. Under the condition of liquid nitrogen cooling, the unreacted magnesium oxide and calcium oxide are not crystallized in time, thereby achieving the effect of most of them being encapsulated by the liquid phase.
[0023] ——The iron phase is a composition of (C2F-C6AF2-C4AF-C 62 AF) solid solution series, among which C4AF is an important component mineral in silicate cement, with moderate hydration rate and high early and late strength. The mineral components are adjusted by controlling the Al2O3 / Fe2O3 in the raw materials to control the formation of C4AF. When the temperature rises, its hydration rate will also tend to accelerate. Under high temperature conditions, in order to adjust the thickening time of cementing slurry, retarders are usually added. The retarding component delays the hydration reaction process of cement through flocculation and wrapping. The retarding component has a retarding effect on each mineral phase in silicate cement and also delays the dissolution rate of the iron phase. Even under different temperature conditions, the dissolution rate of the iron phase is consistent with the hydration process of cement. When the cement hydration degree is high and begins to solidify, the iron phase in the expansion agent begins to dissolve. After the dissolution reaction is completed, the free lime and periclase begin to react with water and produce expansion.
[0024] ——The expansive agent contains three expansive components, and the expansive effect continues to occur at different stages. First, the iron phase begins to hydrate to form iron hydroxide and aluminum hydroxide, among which aluminum hydroxide reacts with free gypsum and calcium hydroxide generated by hydration of gypsum and cement to form calcium vanadium, which plays an initial expansion role through the volume growth of calcium vanadium; after the iron phase reaction is completed, free lime and periclase contact the aqueous solution. After high-temperature calcination at 1100-1280℃, the reaction activities of free lime and periclase with water are different. Free lime will first react to form calcium hydroxide, forming mid-term expansion; while periclase is in a reburned state, and the activation energy of the reaction with water is higher than that of free lime, and the hydration rate is much lower than the reaction rate of calcium oxide with water, and it mainly bears the late expansion effect. Through the continuous expansion of the three expansive minerals at different stages, it can effectively play a continuous expansion role and effectively resist the chemical shrinkage of cement stone.
[0025] ——Calcium sulfosilicate is a low-temperature cement mineral phase with a certain hydration activity. In terms of raw materials, the content and composition of magnesium-containing raw materials, fluorite, fluorgypsum and gypsum are adjusted to ensure that the lower temperature promotes the formation of the liquid phase, stabilize the calcium sulfosilicate minerals, and increase the content of gypsum. Gypsum reacts with silica and calcium oxide brought in by other raw materials to form calcium sulfosilicate. Even if the temperature fluctuates during the production process, calcium sulfosilicate decomposes at a higher temperature to form α'-C2S and free gypsum. These minerals still have more hydration activity at 30-90°C than under normal temperature hydration conditions. At the same time, free gypsum is formed during the cooling process to ensure the formation of calcium sulfosilicate. The mass ratio of aluminum oxide to iron oxide is controlled to form highly reactive anhydrous calcium sulfoaluminate, which effectively avoids the effect of adding expansion agents on the strength of cement stone. During the hydration process, gypsum will react with free lime and aluminum hydroxide to form calcium vanadium, which enhances the expansion of the expansion agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD diffraction pattern of the expanding agent of Example 1 of the present invention; Figure 2 This is an EDS surface scan of the free lime of the expansion agent in Example 2 of the present invention.
[0027] Figure 3 This is an EDS surface scan of the expansion agent periclase in Example 2 of the present invention.
[0028] Figure 4 This is an EDS surface scan of the expansion agent ferric oxide in Example 2 of the present invention.
[0029] Figure 5 This is an EDS surface scan of aluminum oxide, the expansion agent in Example 2 of the present invention.
[0030] Figure 6 This is a petrographic picture of the expansion agent in Example 2 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1 As a preferred embodiment of the present invention, this embodiment provides an expansion agent for cementing cementitious materials, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them.
[0033] The raw materials of the expander are composed of calcium materials, magnesium materials, iron, aluminum materials and other materials; Among them, the calcium material is selected from 6 parts of limestone and 62 parts of carbide slag; the CaO content in the limestone is 54.82%, and the SiO2 content is 0.19%, and the CaO content in the carbide slag is 68.21%, and the SiO2 content is 1.20%; The magnesium material is 10 parts of magnesite, and the MgO content in the magnesite is 45.85%; The iron and aluminum materials are 9 parts of sulfuric acid slag and 5 parts of bauxite. The Fe2O3 content in the sulfuric acid slag is 72.2, and the Al2O3 content in the bauxite is 71.20%; The other materials selected are 1 part of fluorite and 7 parts of anhydrite. The F content in the fluorite is 27.21%, and the SO3 content in the anhydrite is 40.18%.
[0034] The composition of the expansion agent is controlled to be SiO2=1.73%, SO3=3.23%, and Al2O3:Fe2O3=0.74.
[0035] The particle distribution of the above calcium and magnesium materials is V 45μm-200μm =56.0%, particle size greater than 200μm = 3.5%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm =36.0%, particles with a size greater than 200μm = 0.12%.
[0036] The mineral composition of the obtained expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are coated by tetracalcium aluminoferrate. The specific surface area is adjusted to 240m according to the application scenario. 2 / kg. The applicable temperature of the expansion agent is 30-90℃, and the dosage is 5.0% of the mass fraction of the cementing material.
[0037] As an example of this embodiment, the limestone and carbide slag selected as the above-mentioned calcium materials can also be replaced in combination with marble or white mud; the dolomite selected as the above-mentioned magnesium material can also be replaced by dolomite or sepiolite; the fluorite and anhydrite selected as the above-mentioned other materials can also be replaced in combination with dihydrate gypsum, mixed gypsum, desulfurized gypsum, phosphogypsum or fluorite.
[0038] Example 2 As another preferred embodiment of the present invention, this embodiment provides an expansion agent for cementing cementitious materials, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them.
[0039] The raw material composition of the expansion agent is calcium material, magnesium material, iron, aluminum material and other materials; among them, the calcium material is selected from 10 parts of white mud and 40 parts of carbide slag; the CaO content of the white mud is 52.02%, and the SiO2 content is 1.10%; the CaO content of the carbide slag is 69.1%, and the SiO2 content is 1.15%; The magnesium material is 8 parts of magnesite and 10 parts of sepiolite, the MgO content of magnesite is 45.85%; the MgO content of sepiolite is 21.42%; The iron and aluminum materials are 13 parts of magnetite and 11 parts of aluminum ash, the content of Fe2O3 in magnetite is 69.45%, and the content of Al2O3 in aluminum ash is 69.23%; The other materials selected are 0.8 parts of fluorite and 7.2 parts of dihydrate gypsum. The F content in the fluorite is 28.46%, and the SO3 content in the dihydrate gypsum is 33.45%.
[0040] The composition of the expansion agent is controlled as SiO2=3.53%, SO3=3.56%, Al2O3:Fe2O3=0.70%.
[0041] The particle distribution of the above calcium and magnesium materials is V 45μm-200μm =35.0%, particle size greater than 200μm = 2.1%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm =40.0%, particles with a size greater than 200μm = 1.0%.
[0042] The mineral composition of the obtained expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are coated by tetracalcium aluminoferrate. The specific surface area is adjusted to 298m according to the application scenario. 2 / kg. The applicable temperature of the expansion agent is 30-90℃, and the dosage is 9.0% of the mass fraction of the cementing material.
[0043] Example 3 As another preferred embodiment of the present invention, this embodiment provides an expansion agent for cementing cementitious materials, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them.
[0044] The raw material composition of the expansion agent is calcium material, magnesium material, iron, aluminum material and other materials; among them, the calcium material is 53 parts of carbide slag; the CaO content of the carbide slag is 69.51%, and the SiO2 content is 1.05%; The magnesium material is 6 parts of magnesite and 8 parts of dolomite, the MgO content of magnesite is 42.63%; the MgO content of dolomite is 20.45%; The iron and aluminum materials are 10 parts of copper slag, 3 parts of steel slag, 17 parts of bauxite and 4 parts of high-alumina bauxite. The Fe2O3 content in the copper slag is 69.45%, the Fe2O3 content in the steel slag is 50.00%; the Al2O3 content of bauxite and high-alumina bauxite is 69.23%, and the Al2O3 content of high-iron bauxite is 29.00%; The other materials selected are 0.5 parts of fluorite and 8.5 parts of phosphogypsum. The F content in fluorite is 28.46%, and the SO3 content in phosphogypsum is 33.45%.
[0045] The composition of the expansion agent is controlled as SiO2=3.53%, SO3=1.46%, Al2O3:Fe2O3=0.70%.
[0046] The particle distribution of the above calcium and magnesium materials is V 45μm-200μm =50.0%, particle size greater than 200μm = 1.2%; iron and aluminum materials are mixed and ground, and V is controlled in the particle distribution 45μm-200μm =25.0%, particles with a size greater than 200μm = 0.9%.
[0047] The mineral composition of the obtained expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are coated by tetracalcium aluminoferrate. The specific surface area is adjusted to 260m according to the application scenario. 2 / kg. The applicable temperature of the expansion agent is 30-90℃, and the dosage is 7.0% of the mass fraction of the cementing material.
[0048] Example 4 As another preferred embodiment of the present invention, this embodiment provides an expansion agent for cementing cementitious materials, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them.
[0049] The raw materials of the expansion agent are composed of calcium materials, magnesium materials, iron, aluminum materials and other materials; among them, the calcium materials are 40 parts of marble and 30 parts of carbide slag; the CaO content in marble is 51.21%, and the SiO2 content is 1.3%; the CaO content in carbide slag is 65.23%, and the SiO2 content is 1.5%; The magnesium material selected is 11 parts of magnesite, and the MgO content in the magnesite is 39.21%; The iron and aluminum materials are 5 parts of bauxite and 7 parts of magnetite, the Fe2O3 content in magnetite is 65.12%, and the Al2O3 content in bauxite is 52.13%; The other materials selected are 0.6 parts of fluorite and 6.4 parts of dihydrate gypsum. The F content in fluorite is 19.21%, and the SO3 content in dihydrate gypsum is 28.56%.
[0050] The composition of the expanding agent is controlled as SiO2=1.56%, SO3=2.10%, Al2O3:Fe2O3=0.66.
[0051] The particle distribution of the above calcium and magnesium materials is V 45μm-200μm =45.2%, particle size greater than 200μm = 2.1%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm =33.2%, particles with a size greater than 200μm = 1.2%.
[0052] The mineral composition of the obtained expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are coated by tetracalcium aluminoferrate. The specific surface area is adjusted to 280m according to the application scenario. 2 / kg. The applicable temperature of the expansion agent is 30-90℃, and the dosage is 10.0% of the mass fraction of the cementing material.
[0053] Example 5 As another preferred embodiment of the present invention, this embodiment provides an expansion agent for cementing cementitious materials, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them.
[0054] The raw material composition of the expansion agent is calcium material, magnesium material, iron, aluminum material and other materials; among them, the calcium material is 30 parts of limestone, in which the CaO content is 54.23% and the SiO2 content is 0.12%; The magnesium material is 30 parts of dolomite, and the MgO content in dolomite is 21.53%; The iron and aluminum materials are 12 parts of bauxite and 8 parts of sulfuric acid slag, with a Fe2O3 content of 71.02% and an Al2O3 content of 66.89% in bauxite; The other materials selected are 1 part of fluorite and 9 parts of dihydrate gypsum. The F content in fluorite is 19.21%, and the SO3 content in dihydrate gypsum is 33.12%.
[0055] The composition of the expanding agent is controlled as SiO2=2.30%, SO3=2.20%, Al2O3:Fe2O3=0.71.
[0056] The particle distribution of the above calcium and magnesium materials is V 45μm-200μm =36.9%, particle size greater than 200μm = 0.5%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm =30.0%, particles with a size greater than 200μm = 1.2%.
[0057] The mineral composition of the obtained expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are coated by tetracalcium aluminoferrate. The specific surface area is adjusted to 300m according to the application scenario. 2 / kg. The applicable temperature of the expansion agent is 30-90℃, and the dosage is 5.6% of the mass fraction of the cementing material.
[0058] Example 6 As another preferred embodiment of the present invention, this embodiment provides an expansion agent for cementing cementitious materials, wherein the expansion agent is obtained by grinding and mixing expansion agent raw materials, pressing them into cakes, calcining them at a high temperature of 1100°C-1280°C, and then grinding them.
[0059] The raw material composition of the expansion agent is calcium material, magnesium material, iron, aluminum material and other materials; among them, the calcium material is 45 parts of white mud; the CaO content in the white mud is 49.23%, and the SiO2 content is 2.0%; The magnesium material is 20 parts of magnesite, and the MgO content in the magnesite is 37.25%; The iron and aluminum materials selected are 12 parts of bauxite and 23 parts of pyrite, the Fe2O3 content in the pyrite is 50.19%, and the Al2O3 content in the bauxite is 59.14%.
[0060] The composition of the expanding agent is controlled as SiO2=1.56%, SO3=2.10%, Al2O3:Fe2O3=0.66.
[0061] The particle distribution of the above calcium and magnesium materials is V 45μm-200μm =56.0%, particle size greater than 200μm = 4.9%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm =35.0%, particles with a size greater than 200μm = 1.2%.
[0062] The mineral composition of the obtained expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are coated by tetracalcium aluminoferrate. The specific surface area is adjusted to 260m according to the application scenario. 2 / kg. The applicable temperature of the expansion agent is 30-90℃, and the dosage is 6.5% of the mass fraction of the cementing material.
[0063] Comparative Example 1 In order to highlight the performance of the expansion agent for cementing cementing material proposed in the present invention, this comparative example is specially set up. In this comparative example, limestone is used as raw material, crushed and sent into a high-temperature furnace, calcined at 1200°C for 30 minutes to obtain calcium oxide expansion agent, and then ball-milled into powder, with a specific surface area controlled to be 285m 2 / kg.
[0064] Comparative Example 2 In order to highlight the performance of the expansion agent for cementing cementing material proposed in the present invention, this comparative example is specially set up. In this comparative example, magnesite is used as raw material, crushed and sent into a high-temperature furnace, calcined at 1200°C for 30 minutes to obtain magnesium oxide expansion agent, and then ball-milled into powder, with a specific surface area controlled to be 276m 2 / kg.
[0065] Test Example 1 According to the above-mentioned Examples 1-4 and Comparative Examples 1-2, 3% of the mixture was added to the G-grade oil well cement, and cement slurry was prepared according to the relevant provisions of GB / T19139, wherein the mixing water accounted for 44% of the mass of the cementing cement. The prepared cement slurry was poured into the expansion ring and the strength model for molding, and respectively placed in a water bath at 30°C, 60°C, and 90°C for curing. The expansion values of the cement at 1d, 3d, and 7d were tested according to the relevant requirements of GB / T33293-2016. The specific test results are shown in Tables 1, 2, and 3.
[0066] Table 1 shows the expansion rate and compressive strength of the expansion agent at 30°C Table 2 shows the expansion value of the expansion agent at 60°C Table 3 shows the expansion value of the expansion agent at 90°C According to the data in the above table, under the condition of the same water-cement ratio, the expansion values of schemes 1-4 at different curing temperatures and different ages are significantly better than those of the control samples, indicating that during the hydration process, due to the different expansion sources of the expansive agent, during the hydration process of G-class oil well cement, a small amount of free gypsum and gypsum react with tricalcium aluminate and iron phase water to form ettringite to provide an early hydration mineral skeleton, and provide an early expansion source and early strength support material. The iron phase and glass phase that encapsulate the free calcium oxide and periclase are also consumed at the same time to form ettringite to increase the density of the silicate hydration product; immediately after the iron phase is consumed, the calcium hydroxide formed by the moderate hydration reaction of the free calcium oxide particles encapsulated inside expands in volume and fills the space occupied by the water after the reaction of silicate minerals, and the water hydrates the calcium silicate gel and ettringite and the expansive agent to produce alternating hydration products; periclase continues to hydrate to form magnesium hydroxide after the external encapsulation is hydrated, and continues to fill part of the space of water and cementitious products, so that the density of cement paste is further improved, and at the same time, the cement strength is further improved.
[0067] The expansion agent compensates for shrinkage and continues to expand during hydration, making the bonding performance of the casing and cement stone good. From the data of Schemes 1-4 and the comparative samples, it can be seen that with the increase of curing temperature, the gypsum in the base material (G-grade oil well cement) reacts with the tricalcium aluminate and iron phase in the cement to form ettringite, which will not decompose at low temperatures (30-60°C). The stability of ettringite is relatively high, and the expansion performance is better than that of the comparative samples 1-2. Under high-temperature curing conditions (90°C), ettringite becomes unstable and easy to decompose, that is, Scheme 3-4, with lower sulfur trioxide, controls lower free gypsum and calcium sulfosilicate content, has a certain inhibitory effect on the early formation of ettringite at high temperature, and the hydration of the encapsulated free calcium oxide and periclase assists the expansion, effectively controlling the shrinkage of the entire process, achieving micro-expansion of cement stone and reducing the shrinkage of high-temperature cement stone. And the expansion performance is positively correlated with the strength of cement stone.
[0068] The expansion agent in Example 1 was subjected to phase analysis, and the Figure 1 As shown, it is confirmed that there are free calcium oxide and periclase in the expansion agent, and there are a large amount of iron phase, among which the content of tetracalcium aluminoferrite is relatively high, it contains a small amount of low-temperature mineral calcium sulfosilicate, and there is a certain amount of free gypsum. This is consistent with the mineral design in the present invention. Figure 2 , Attachment Figure 3 , Attachment Figure 4 and attached Figure 5 The electron microscope analysis of each mineral of the expansion agent of Example 2 is shown in Figure 2. Through EDX analysis, it can be seen that periclase and free calcium oxide are evenly distributed, and few large-particle ore nests are formed. Instead, they are evenly wrapped by the iron phase and the glass phase, which can effectively regulate the hydration reaction of free calcium oxide and periclase. Figure 6It can also be concluded from the petrographic analysis diagram that the free calcium oxide with colorful pockmarked morphology and the periclase minerals with straight edges and raised black edges are uniformly wrapped by the iron phase and the glass phase, which more intuitively reflects the sintering process of the expansion agent.
[0069] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. An expansion agent for cementing gelling material, characterized in that: The expander is prepared by grinding and mixing the expander raw materials into cakes, calcining at 1100°C-1280°C and then grinding them. In parts by weight, the expansion agent raw material comprises Calcium materials: 30-70 parts, magnesium materials: 10-30 parts, iron and aluminum materials: 12-35 parts, other materials: 0-10 parts; The mineral composition of the expansion agent includes free lime, periclase, iron phase, tetracalcium aluminoferrate and calcium sulfosilicate, wherein the free lime and periclase are wrapped by tetracalcium aluminoferrate.
2. The expansion agent for cementing gelling material according to claim 1, characterized in that: The applicable temperature of the expansion agent is 30°C-90°C.
3. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The chemical composition of the expander raw material is controlled within the range of SiO2≤3.5%, SO3>2.4%, and Al2O3:Fe2O3>0.64%.
4. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The particle distribution of the calcareous material is V 45μm-200μm ∈[35%, 60%], particles with a particle size greater than 200 μm <5%; the particle distribution in the magnesium material is V 45μm-200μm ∈[35%,60%], particle size greater than 200μm particles <5%; iron and aluminum materials are mixed and ground, and the particle distribution is controlled by V 45μm-200μm ∈[25%,40%], particles with a size greater than 200μm <2%.
5. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The calcareous material is any one or any combination of a mixture of carbide slag and limestone, marble and white mud, wherein the CaO content is ≥52.00% and the SiO2 is ≤1.5%.
6. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The magnesia material is any one or more combinations of dolomite, magnesite and sepiolite, wherein the MgO content in dolomite is ≥19.00%, the MgO content in magnesite is ≥40.00%, and the MgO content in sepiolite is ≥19.0%.
7. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The iron material among the iron and aluminum materials is copper slag, magnetite, sulfuric acid slag or steel slag, and the F2O3 content is ≥50.00%; the aluminum material among the iron and aluminum materials is bauxite, aluminum ash slag or high-iron bauxite, wherein the Al2O3 content of bauxite is ≥70.00%, SiO2≤2.0, the aluminum content of aluminum ash slag is ≥65.00%, SiO2≤2.0, the Al2O3 content of high-iron bauxite is ≥29.00%, and the F2O3 content is ≥15.00%.
8. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The other materials are fluorite and dihydrate gypsum, anhydrite, mixed gypsum, desulfurized gypsum, phosphogypsum or fluorinated gypsum, wherein the F ion content in the fluorite is ≥25.00%, and the SO3 content in the gypsum is ≥30.00%.
9. The expansion agent for cementing gelling material according to claim 1 or 2, characterized in that: The specific surface area of the expansion agent is controlled at 240-300m 2 / kg.
10. Use of the expansion agent according to any one of claims 1 to 9 in cementing gelling materials, wherein the amount used is 5% to 10% by mass of the cementing gelling materials.
Citation Information
Patent Citations
Oil well cement crystal expansion agent and preparation thereof
CN101481605A
Toughening expanding agent for well cementation cement paste and toughening micro-expansion cement paste system
CN111454032A
Temperature control type concrete expanding agent
CN111875283A
Magnesium slag-based expansion material as well as preparation method and application thereof
CN116693228A
Wide-temperature-zone well cementation expanding agent and well cementation expanding cement slurry system containing same
CN117658507A